Preterm Birth: Born Too Soon for the Developing Airway Epithelium? - Evans, Denby Jai (Curtin University, 2023)
Preterm birth is associated with poor respiratory health across the life course, yet treatment options are limited by a lack of knowledge regarding the underlying mechanisms. This PhD investigated the airway epithelium as a contributing factor to preterm lung disease and established the first model of the very preterm airway epithelium following discharge from neonatal intensive care. The study identified several structural and functional abnormalities within the epithelial cells, paving the way for novel interventions.